Construção e validação de um questionário para análise de concepções bioéticas - Silva, Paloma Rodrigues da [UNESP]; Araujo, Elaine Sandra Nicolini Nabuco de; Caldeira, Ana Maria de Andrade [UNESP]; Carvalho, Graça (My University, 2012)
In this paper we describe the stages of a quantitative questionnaire development that allows the investigation of conceptions about bioethical values inherent to the scientific activity. This questionnaire was statistically and semantically validated and developed according to the Likert scale. The relevance of this instrument is given by the fact that, unlike what happens in European countries, quantitative research in Brazil has little educational traditions. Therefore, this work is intended to subsidize the use of quantitative methods in Education research that lack such tools.

En este trabajo se describen las etapas del desarrollo de un cuestionario cuantitativo que permite investigar las concepciones acerca de los valores bioéticos inherentes a la actividad cienơfi ca. Este cuestionario fue validado estadísticamente y semánticamente, y fue desarrollado tomando como base la escala de Likert. La relevancia de este instrumento está dada por el hecho de que, a diferencia de lo que ocurre en los países europeos, la investigación cuantitativa en Brasil tine poca tradición educativa. Este trabajo tiene por objeto, por tanto, subsidiar el uso de los métodos cuantitativos en la investigación en educación, que carecen de tales herramientas.

Neste artigo objetivamos descrever as etapas do processo de elaboração de um questionário quantitativo que permita investigar as concepções sobre valores bioéƟ cos inerentes à atividade científica. Validado semântica e estatisticamente, o questionário foi desenvolvido tendo por base a escala do tipo Likert. A relevância deste instrumento se dá pelo fato de que, diferentemente do que ocorre nos países europeus, as pesquisas quantitativas educacionais no Brasil têm pouca tradição. Este trabalho destina-se, portanto, a subsidiar o uso de métodos quantitativos nas pesquisas em Educação, que carecem de instrumentos deste tipo.
Construction and validation of a questionnaire for the analysis of bioethical conceptions
Construcción y validación de un cuesƟ onario para análisis de concepciones bioéticas
Keywords: Education; Bioethics; Methodology; Educación; Bioética; Metodología; Ensino; Bioética; Metodologia